A current perspective for photocatalysis towards the hydrogen production from biomass-derived organic substances and water. (17th July 2020) - Huang, Chao-Wei; Nguyen, Ba-Son; Wu, Jeffrey C.-S.; Nguyen, Van-Huy
Abstract: Recently, an increasing interest has been devoted to produce chemical energy – hydrogen (H2 ) by converting sustainable sunlight energy via water splitting and reforming of renewable biomass-derived organic substances. These photocatalytic processes are very promising, sustainable, economic, and environment-friendly. Herein, this article gives a concise overview of photocatalysis to produce H2 as solar fuel via two approaches: water splitting and reforming of biomass-derived organic substances. For the first approach – photocatalytic water splitting, there are two reaction types have been used, including photoelectrochemical (PEC) and photochemical (PC) cell reactions. For the second approach, biomass-derived oxygenated substrates could undergo selective photocatalytic reforming under renewable solar irradiation. Significant efforts to date have been made for photocatalysts design at the molecular level that can efficiently utilize solar energy and optimize the reaction conditions, including light irradiation, type of sacrificial reagents. Critical challenges, prospects, and the requirement to give more attention to photocatalysis for producing H2 are also highlighted. Highlights: Photocatalytic processes open opportunities for the development of renewable energy. Hydrogen from photocatalytic water splitting and reforming of biomass are reviewed. Critical challenges, prospects and attentions of photocatalysis for producing H2 are highlighted.